The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.3758/bf03194558
|View full text |Cite
|
Sign up to set email alerts
|

Modulations of the processing of line discontinuities under selective attention conditions?

Abstract: We examined whether the processing of discontinuities involved in figure-ground segmentation, like line ends, can be modulated under selective attention conditions. Subjects decided whether a gap in collinear or parallel lines was located to the right or left. Two stimuli were displayed in immediate succession. When the gaps were on the same side, reaction times (RTs) for the second stimulus increased when collinear lines followed parallel lines, or the reverse, but only when the two stimuli shared the same or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…# These are sometimes visible, like in the Ehrenstein illusion ( Figure 2, Gove et al, 1995 ;Lesher and Mingolla, 1993 ;von der Heydt and Peterhans, 1989 ;Westheimer and Li, 1996). In our stimuli, perpendicular lines are not consciously perceived, but are nevertheless produced (Giersch, 2001 ;Giersch and Fahle, 2002 ;Giersch and Caparos, 2005 ;Gurnsey et al, 1999 ;von der Heydt and Peterhans, 1989).…”
Section: Collinear Elementsmentioning
confidence: 51%
See 2 more Smart Citations
“…# These are sometimes visible, like in the Ehrenstein illusion ( Figure 2, Gove et al, 1995 ;Lesher and Mingolla, 1993 ;von der Heydt and Peterhans, 1989 ;Westheimer and Li, 1996). In our stimuli, perpendicular lines are not consciously perceived, but are nevertheless produced (Giersch, 2001 ;Giersch and Fahle, 2002 ;Giersch and Caparos, 2005 ;Gurnsey et al, 1999 ;von der Heydt and Peterhans, 1989).…”
Section: Collinear Elementsmentioning
confidence: 51%
“…When the gap to be detected is between parallel elements, however, the two line terminations forming the gap produce a perpendicular line that is in exactly the same place as the gap and closes the stimulus (Figure 2b). We have suggested that the processing of line terminations is modulated in healthy volunteers (Giersch and Caparos, 2005 ;Giersch and Fahle, 2002), and that lorazepam affects this modulation (review in Giersch, 2001 ;Lorenceau et al, 2005), which explains why lorazepam-treated subjects separate elements even when they are collinear, at least when contour processing is modulated. Several studies have suggested that the effects of lorazepam on the processing of line terminations thus impairs the binding of the local elements composing the object (Giersch et al, 1997 ;Giersch and Lorenceau, 1999 ;Lorenceau et al, 2005).…”
Section: Collinear Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The output of this integration process is then forwarded to higher-level regions responding to global pattern structure (e.g., the lateral occipital complex [LOC], more anterior temporal cortex). Consistent with this view, lesions to intermediate visual areas are associated with disorders in the organization of visual elements into recognizable whole patterns (Giersch, 2002;Milner et al, 1991;Riddoch & Humphreys, 1987).…”
Section: Introductionmentioning
confidence: 51%
“…We argue that local–global processing, that is, the classical distinction between the coding of details and global forms (Navon, 1977), is not enough to resolve such cases, because neither pair of individuals corresponds to either local information (one individual) or global information (the crowd). It does not suppress the risk of fragmentation that may occur when two objects that belong to two different groups must be considered as one (Giersch & Caparos, 2005; Giersch & Fahle, 2002). This question is all the more crucial because it can in fact occur quite often in everyday life, for instance, in cases where visual scenes are rich and complex.…”
Section: Grouping and Schizophreniamentioning
confidence: 99%